2015
DOI: 10.1097/bot.0000000000000261
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Dedicated Orthopaedic Advanced Practice Provider in a Level I Trauma Center

Abstract: Economic Level IV. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
68
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(68 citation statements)
references
References 6 publications
0
68
0
Order By: Relevance
“…Similarly, studies showed that using an ortho-geriatrician-led program for hip fracture patients was associated with improved outcomes in terms of acute hospital LOS (Biber et al, 2013;Gupta, 2014;Lynch, Shaban, & Massey, 2015) and mortality (Zeltzer et al, 2014). We found a few published studies (Collins, Miller, & Kapu, 2014;Hiza, 2015;Jarrett & Emmett, 2009;Morris, 2012) that investigated the role of the Trauma Nurse Practitioner however, we could only find one study (Holte, Sems, & Fruth, 2015)…”
Section: Zierlermentioning
confidence: 88%
See 2 more Smart Citations
“…Similarly, studies showed that using an ortho-geriatrician-led program for hip fracture patients was associated with improved outcomes in terms of acute hospital LOS (Biber et al, 2013;Gupta, 2014;Lynch, Shaban, & Massey, 2015) and mortality (Zeltzer et al, 2014). We found a few published studies (Collins, Miller, & Kapu, 2014;Hiza, 2015;Jarrett & Emmett, 2009;Morris, 2012) that investigated the role of the Trauma Nurse Practitioner however, we could only find one study (Holte, Sems, & Fruth, 2015)…”
Section: Zierlermentioning
confidence: 88%
“…This study clearly demonstrated a decreased acute hospital LOS after implementation of the ONP role. Previous studies (Collins et al., ; Hiza, ; Jarrett & Emmett, ; Morris, ) have shown using Nurse Practitioners for patients with trauma that is, any injured trauma patient, have led to decreased average LOS (Collins et al., ; Hiza, ; Jarrett & Emmett, ; Morris, ) and cost‐savings (Collins et al., ; Hiza, ) without increasing complications (Morris, ), or re‐admission (Morris, ) rates. We found only one study (Holte et al., ) that investigated the impact of the ONP on the care of hip fracture patients which similarly found adding Nurse Practitioners to the orthopaedic trauma team decreased patient LOS without increasing mortality rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous research, researchers have found advanced practice nursing to be as good as or, in some cases, even better than physician‐led care (Cooper, Lindsay, Kinn, & Swann, ; Roche, Gardner, & Jack, ; Wilson, Zwart, Everett, & Kernick, ). Nurse‐led care has been shown to have a positive impact on wait times (Hiza, Gottschalk, Umpierrez, Bush, & Reisman, ; Jennings, Clifford, Fox, O'Connell, & Gardner, ), patient satisfaction (Cooper et al, ; Jennings et al, ; Martinez‐Gonzalez et al, ), and quality of care (Jennings et al, ; Martinez‐Gonzalez et al, ). Still, more research on the subject is needed (Jennings et al, ; Martinez‐Gonzalez et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Nurse-led care has been shown to have a positive impact on wait times (Hiza, Gottschalk, Umpierrez, Bush, & Reisman, 2015;Jennings, Clifford, Fox, O'Connell, & Gardner, 2015), patient satisfaction (Cooper et al, 2002;Jennings et al, 2015;Martinez-Gonzalez et al, 2014), and quality of care (Jennings et al, 2015;Martinez-Gonzalez et al, 2014). Still, more research on the subject is needed (Jennings et al, 2015;Martinez-Gonzalez et al, 2014).…”
mentioning
confidence: 99%